Effect of Price Discount, Instore Display, and Promotion on Impulse Buying - Thamara, Ferdalia; Dandi, Faeza; Maulida, Inayatul; Sanjaya, Vicky F (FEBI UIN Sunan Kalijaga, 2020)
Competition in the business world around the world is getting higher and tighter, every company is always trying to get market share which will always grow every day. For this reason, companies must increase consumer satisfaction by further increasing consumer attractiveness through unplanned purchases or impulse buying. Impulse Buying is defined as the behavior of consumers who make purchases directly and there is no prior plan that is done quickly and does not require much evaluation. This study is entitled The Effect of Price Discount, Instore Display, and Promotion on Impulse Buying. This study aims to determine the effect of price discouns, instore displays, and promotions on impulse buying using a sample of 100 respondents. The data collection method is done by distributing questionnaires. The data were analyzed quantitatively using an SPLS-based program. The analysis method used is validity test and reliability test. And the results of this study are the effect of price discounts, instore displays, and promotions have a significant effect on impulse buying.Keywords :Price Discount, Instore Display, Promotion, Impulse Buying